“Let’s get back to normal”: emotions mediate the effects of persuasive messages on willingness to vaccinate for COVID-19 - Muis, Krista R.; Kendeou, Panayiota; Kohatsu, Martina; Wang, Shuting (Frontiers in Public Health, 2024)
Objective We examined the effectiveness of three different messages for persuading individuals to get vaccinated against COVID-19, and the role that emotions play in persuasion. Methods Four hundred-thirty-six participants reported their concern about the COVID-19 pandemic and confidence/hesitancy toward vaccines. Participants were randomly assigned to one of three text conditions: (1) self-interest: a persuasive message that focused on how much of a “serious threat COVID-19 is to you,” and to get vaccinated to “protect yourself”; (2) self-interest + altruistic: a persuasive message that focused on the “threat to you and your community” and to get vaccinated to “protect you and your loved ones”; (3) self-interest + altruistic + normal: a persuasive message that included (2) but added “This is the only way we can get back to a normal life.”; and, (4) a baseline control: no text. After reading, participants reported their emotions toward COVID-19 vaccines and their willingness to get vaccinated. Results Individuals in the self-interest + altruistic + normal condition were more willing to get vaccinated compared to the control condition and self-interest + altruistic condition. However, there were no differences in willingness between the self-interest + altruistic + normal condition and the self-interest condition. Moreover, emotions mediated relations between vaccine confidence/hesitancy and willingness. Conclusion A message that focuses on “getting back to normal” can achieve important public health action by increasing vaccine uptake to protect the population. Future work is needed across multiple countries and contexts (i.e., non-pandemic) to assess message effectiveness.